2022
DOI: 10.3389/fpsyg.2022.954964
|View full text |Cite
|
Sign up to set email alerts
|

Privacy concerns toward short-form video platforms: Scale development and validation

Abstract: Privacy concerns can effectively predict behavioral intention between users and short-form video platforms, but existing studies lack of multidimensional scales to measure privacy concerns towards short-form video platforms. To this end, this study took privacy concerns theory as the theoretical foundation to develop and validate a multidimensional privacy concerns scale in short-form video platforms by referring to the development of Smith, Milberg and Burke' multidimensional scale of concerns for information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Consumers also pay attention to privacy security. Research has found that user privacy leakage can significantly affect consumers' trust in a platform and reduce loyalty (Wang et al, 2022). The platform's management capabilities, reliability (Akhmedova et al, 2021) and service remediation (Hogreve et al, 2019) are effective ways to address ethical concerns.…”
Section: Subject Diversity On Trust Of Platforms 1213mentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers also pay attention to privacy security. Research has found that user privacy leakage can significantly affect consumers' trust in a platform and reduce loyalty (Wang et al, 2022). The platform's management capabilities, reliability (Akhmedova et al, 2021) and service remediation (Hogreve et al, 2019) are effective ways to address ethical concerns.…”
Section: Subject Diversity On Trust Of Platforms 1213mentioning
confidence: 99%
“…Consumers also pay attention to privacy security. Research has found that user privacy leakage can significantly affect consumers' trust in a platform and reduce loyalty (Wang et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this model and instrument have been extended and empirically validated to explore related phenomena, specifically privacy concerns in the context of social media (e.g. social media video sharing: Wang et al ., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notably, this model and instrument have been extended and empirically validated to explore related phenomena, specifically privacy concerns in the context of social media (e.g. social media video sharing: Wang et al, 2022). Koohang et al (2018Koohang et al ( , p. 1210) introduced the term "social media privacy concerns" (SMPC) as an extension of Internet privacy concerns, defining it as the extent to which users worry about how social media platforms handle their personal information.…”
Section: Introductionmentioning
confidence: 99%